Probabilistic capacity of structural insulated panel and its use for calibrating codified design - ICASP14; Hong, Hanping; Chui, Y. H.; Yang, Shucheng (My University, 2023)
In the present study, we first report the experimental studies focused on the investigation of the behavior of a structural insulated panel (SIP) subjected to various load cases. The experimental results are then used as the basis to develop and implement finite element (FE) models that can be used to predict the response of SIP to compression, bending, and racking loads. Uncertainty propagation analysis is carried out using developed FE models and considering the uncertainty in material properties to provide a probabilistic characterization of the capacity of SIP-spline wall/floor system. Finally, a probability distribution fitting exercise was carried out to identify the preferred probability distribution for the ultimate capacity of the SIP shearwall subjected to racking load, the SIP assembly subjected to out-of-plane bending in the major direction, and the SIP shearwall subjected to compression. The fitting and a statistical criterion indicates that lognormal distribution, Weibull distribution, and Gumbel distribution are preferred for the ultimate capacity of the SIP-spline wall/floor subjected to racking, bending and compression loads, respectively.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED